Contrasting monetary policies within the MERCOSUR experiment - Andrade, Joaquim Pinto de; Silva, Maria Luiza Falcao; Carneiro, Francisco Galrão (Economia Aplicada, 2000)
The formation of global markets has become, not unsurprisingly, a matter ofintense concern for many developing countries, fearful for their own economic and political survival as autonomous entities in the "new world economic order" As a result of this concern, many developing countries are seeking security by forming regional economic blocs, involving trading agreements and preferences and, in some cases, plans for eventual monetary union. This paper examines the Latin American regional integration experience, specifically the Common Market of the South (Mercado Comun del Sur or MERCOSUR), focusing on macroeconomic monetary policies implemented by Argentina and Brazil the major MERCOSUR'S member countries.